Neuroscience nursing increased intracranial pressure - Lower, Judith "Ski" (Baltimore : Williams & Wilkins, 1995)
This video series provides a basis for understanding and assesing the neurologic system. Demonstrations of cranial nerve assessment, motor strength and function, and a neurologic emergency insure that viewers will have an understanding of not only why these aspects are evaluated, but how to accurately measure the patient's response.
Keywords: Neurological Nursing